2021
DOI: 10.1016/j.omtn.2021.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomics reveals the landscape of intra-tumoral heterogeneity and transcriptional activities of ECs in CC

Abstract: Cervical cancer (CC) is the fourth leading cause of deaths in gynecological malignancies. Although the etiology of CC has been extensively investigated, the exact pathogenesis of CC remains incomplete. Recently, single-cell technologies demonstrated advantages in exploring intra-tumoral diversification among various tumor cells. However, single-cell transcriptome analysis (single-cell RNA sequencing [scRNA-seq]) of CC cells and microenvironment has not been conducted. In this study, a total of 20,938 cells fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 48 publications
2
64
0
Order By: Relevance
“…To the best of our knowledge, this is one of the first few studies to comprehensively characterize a single-cell atlas of cervical cancer patients in China and worldwide (60).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is one of the first few studies to comprehensively characterize a single-cell atlas of cervical cancer patients in China and worldwide (60).…”
Section: Discussionmentioning
confidence: 99%
“…10x genomic single-cell RNA-sequencing files of cervical cancer and normal tissue: GSE168652 (GSM5155196 and GSM5155197) were downloaded from NCBI GEO [ 33 ]. The expression matrix was loaded into R and analyzed by Seurat package (version 4.0.3) [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…TAGLN2, KLF5, STAT1 and STAT2 (7). ScRNA sequencing revealed that 2590 genes were differentially expressed between TECs isolated from human hepatocellular carcinoma and NECs isolated from normal liver tissues (61).…”
Section: Heterogeneity Of Tumor-specific Endothelial Cellsmentioning
confidence: 99%
“…Initial hypotheses suggested that TECs were genetically stable normal somatic cells that were not prone to mutation and drug resistance and remained consistent in various tumors, which would allow multiple types of cancer to be treated by a single antiangiogenic drug (5). However, in recent years, many researchers have found that TECs are not ordinary somatic cells but rather are heterogeneous in many aspects relative to normal endothelial cells (NECs), which contradicts previous assumptions (6,7). Therefore, the study of TECs will provide targets or directions for tumor therapy.…”
Section: Introductionmentioning
confidence: 98%